A COMPARATIVE STUDY BETWEEN THE USE OF VSS (VOCABULARY SELF-COLLECTION STRATEGY) AND SVES (STEPHENS VOCABULARY ELABORATION STRATEGY) ON STUDENTS’ VOCABULARY MASTERY AT SMPN I BANTAN IN BENGKALIS REGENCY - Nurbi, Leni Nurpitasari (Journal of Education and Teaching, 2022)
The main purpose of this research was to find out the significant difference on students’ vocabulary mastery between using VSS (Vocabulary Self-Collection Strategy) and SVES (Stephens Vocabulary Elaboration Strategy) on students’ vocabulary mastery at SMPN I Bantan in Bengkalis Regency. The design of this research was a comparative study with a comparative quasi-experimental design. This research used multiple choice test and questionnaire. The data were analyzed by using Paired Sample T-test, Independent Sample T-test and Effect Size. The results of this research were; first, the significant effect of using VSS on students’ vocabulary mastery. The researcher found the significant 0.00 < 0.05. Second, the researcher also found the significant effect of using SVES on students’ vocabulary mastery. The researcher found the significant 0.00 < 0.05. Last, the researcher found the significant difference in vocabulary mastery between students taught by using VSS and SVES. The significant value was 0.022 < 0.05. In conclusion, VSS is more effective than SVES to improve students’ vocabulary mastery. The mean gain score of VSS was higher than the mean gain score of SVESS (18.48 > 15.87).      Key Word: VSS (Vocabulary Self-Collection Strategy), SVES (Stephens Vocabulary Elaboration Strategy), Vocabulary Mastery.